PENDEKATAN STEM DALAM MENJAWAB TANTANGAN PENDIDIKAN ABAD KE-21 DI INDONESIA: STUDI LITERATUR - Widy Dwi Lestari; Sri Aswaidar Miza; Dwi Feriwanti; Afrun Akmal; Rosynanda Nur Fauziah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Twenty-first century education requires students to possess critical, creative, collaborative, and communicative thinking skills, as well as adequate literacy and numeracy competencies. However, the education system in Indonesia still faces various challenges, including low levels of higher-order thinking skills, disparities in the utilization of educational technology, and the need for contextual and interdisciplinary learning approaches. One approach considered relevant in addressing these challenges is the Science, Technology, Engineering, and Mathematics (STEM) approach. This study aims to analyze the role and relevance of the STEM approach in responding to the challenges of twenty-first century education in Indonesia through a literature review method. The research method employed is a literature study that examines scientific articles, conference proceedings, and both national and international publications related to STEM-based learning. The findings indicate that the STEM approach effectively promotes the development of twenty-first century skills, enhances students’ scientific literacy and numeracy, and fosters meaningful and contextual learning experiences. Therefore, the STEM approach has significant potential to be implemented as an innovative instructional strategy to support educational transformation and improvement in Indonesia.